2018
DOI: 10.24297/jap.v14i2.7446
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thermally Evaporated CdSe1-XSX Thin Films for Solar Cells Applications

Abstract: Binary semiconductor CdSe and CdS thin films are widely used for optoelectronic devices and window materials. The formation of ternary CdSe1-xSx thin films improves the physical characteristics of the binary CdSe thin films. The importance of CdSe1-xSx thin film is the change of band gap when incorporating S into the CdSe. This change in energy gap recommends CdSe1-xSx thin film for photovoltaic and photoconductive cells applications. In this work, polycrystalline CdSe1-xSx thin films have been grown in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The predominant orientation of the (002) peak confirms the presence of hexagonal wurtzite structure (JCPDS No. 08-0459) of the prepared films at all substrate temperatures [40] and its narrow-natured peaks confirming that the prepared films were in crystalline nature [41]. From the x-ray diffraction pattern, it is observed that the (002) peak intensity was increased with an increase in substrate temperature up to 200 °C and then gets decreased thereafter.…”
Section: X-ray Diffraction Analysissupporting
confidence: 52%
“…The predominant orientation of the (002) peak confirms the presence of hexagonal wurtzite structure (JCPDS No. 08-0459) of the prepared films at all substrate temperatures [40] and its narrow-natured peaks confirming that the prepared films were in crystalline nature [41]. From the x-ray diffraction pattern, it is observed that the (002) peak intensity was increased with an increase in substrate temperature up to 200 °C and then gets decreased thereafter.…”
Section: X-ray Diffraction Analysissupporting
confidence: 52%